Kegiatan Gunungapi Ciremai Jawa Barat dan Pengaruhnya Terhadap Lingkungan di Sekitarnya - Pratomo, Indyo (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTThe Activity of Ciremai Mountain and The Impact Eruption at the SurroundingArea The Ciremai Mountain is one of the active mountain in West Jawa, the last eruptionwas detected between June 1937 to 7 January 1938, it has respite period for 3-112 years.The potential threatening of the eruption was detected by the pirolastica, the rain dustand ballistic explosion, the current and sliding of lava. The complete history of CiremaiMountain and the dangerous area by eruption were discussed hereKeywords: Ciremai, activity, eruption